Assessing the impact of a virtual short-term study-abroad program on Japanese university students' global-mindedness - Brad Deacon; Richard Miles (University of Groningen Press, 2022)
Short-Term Study-Abroad (STSA) programs are popular in Japanese higher education; however, participating students' experiences are under-researched, particularly in areas outside of second-language acquisition. This study empirically assessed the impact of a six-week study-abroad program with a US university (conducted online as a virtual program due to the COVID-19 pandemic) on sophomore Japanese university students' Global-Mindedness (GM). This mixed-methods study employed experimental (n=53) and control (n=82) groups to investigate the following research question: What is the impact of a virtual STSA program on the GM of participating students? Quantitative data were collected at three time periods (pretest/posttest/post-posttest) using a modified version of the 30- item, five-factor GM Scale (GMS, see Hett, 1993). Descriptive statistics and two-way ANOVAanalyses revealed a significant increase in the experimental groups' posttest results, which then returned to similar pretest levels in the post-posttest period. Reflection papers, surveys, and semi-structured interviews informed the qualitative perspective, and findings suggested a need for sustained post-program supportive measures to help maintain students' GM.